Fenologia do subperíodo reprodutivo de Lithraea molleoides, Schinus terebinthifolius e Helietta apiculata em Santa Maria, RS - Cogo, Maurício Ricardo de Melo (2014)
The historical series of phenological data allow the determination of the relationship of the development of species with climate and site conditions of the region. In Brazil phenological data s banks of different native species practically do not exist. Thus, it appears the importance of undertaking work in this area. The aim of this work was to determine the reproductive phenophases subperiod of native plant species Schinus terebinthifolius, Lithraea molleoides (Vell.) and Helietta apiculata Benth, respectively aroeira-vermelha , aroeira-brava and canela-de-veado. The work was carried out in the Botanical Garden of the Federal University of Santa Maria, UFSM, located in the municipality of Santa Maria - RS, (29º42'S; 53o42'W; altitude: 90 m). Phenological observations from August 2010 to August 2014 were performed on ten plants aroeira-vermelha females and ten males, ten plants aroeira-brava females and ten males and four plants canela- de-veado. Were recorded for each plant dates of beginning and end of flowerbud, anthesis, green fruit and ripe fruit. It was found that the variability of the start date and end of the different phenological phases is very high, especially for plants aroeira-vermelha that is generally higher for starting dates of phenophases. It was observed, although the duration of the early and late phases was greater in aroeira-vermelha than in other species.